ABCB5 is a limbal stem cell gene required for corneal development and repair - Ksander, Bruce R. (Nature, 2014)
Corneal epithelial homeostasis and regeneration are sustained by limbal stem cells (LSCs)(1–3), and LSC deficiency is a major cause of blindness worldwide(4). Transplantation is often the only therapeutic option available to patients with LSC deficiency. However, while transplant success depends foremost on LSC frequency within grafts(5), a gene allowing for prospective LSC enrichment has not been identified so far(5). Here we show that ATP-binding cassette, sub-family B, member 5 (ABCB5)(6,7) marks LSCs and is required for LSC maintenance, corneal development and repair. Furthermore, we demonstrate that prospectively isolated human or murine ABCB5-positive LSCs possess the exclusive capacity to fully restore the cornea upon grafting to LSC-deficient mice in xenogeneic or syngeneic transplantation models. ABCB5 is preferentially expressed on label-retaining LSCs(2) in mice and p63α-positive LSCs(8) in humans. Consistent with these findings, ABCB5-positive LSC frequency is reduced in LSC-deficient patients. Abcb5 loss of function in Abcb5 knockout mice causes depletion of quiescent LSCs due to enhanced proliferation and apoptosis, and results in defective corneal differentiation and wound healing. Our results from gene knockout studies, LSC tracing and transplantation models, as well as phenotypic and functional analyses of human biopsy specimens, provide converging lines of evidence that ABCB5 identifies mammalian LSCs. Identification and prospective isolation of molecularly defined LSCs with essential functions in corneal development and repair has important implications for the treatment of corneal disease, particularly corneal blindness due to LSC deficiency.